Las metáforas y las adivinanzas: estudio comparativo entre dos entornos escolares - Calderón Guerrero, Gabriela (Universidad de San Buenaventura - Cali, 2017)
This research is to contrast the results obtained by children in two different school contexts (a public school and a private school) around understanding metaphors in popular riddles. Two schools (with different characteristics), from the city of Queretaro, Mexico, were selected. 30 students (10 second, 10 fourth and 10 sixth grade of primary school) were interviewed, totaling 60. They were asked to respond to metaphorical riddles in two different tasks, the first of them was spontaneous (no options) and the second one was with the support of three different response options. The results show that children of both schools show the same evolutionary tendency in the development of the understanding metaphors and increased coordination and coherence on the establishment of conceptual relations part/whole. We also found that the task mode has a powerful impact in both populations. Finally, although the same evolutionary patterns between the two schools, school children with a focus on comprehension and text production were more successful in solving riddles and metaphors.